Cellular and Molecular Targets of Menthol Actions - Oz, Murat; El Nebrisi, Eslam G.; Yang, Keun-Hang S.; Howarth, Frank C.; Al Kury, Lina T. (Frontiers in Pharmacology, 2017)
Menthol belongs to monoterpene class of a structurally diverse group of phytochemicals found in plant-derived essential oils. Menthol is widely used in pharmaceuticals, confectionary, oral hygiene products, pesticides, cosmetics, and as a flavoring agent. In addition, menthol is known to have antioxidant, anti-inflammatory, and analgesic effects. Recently, there has been renewed awareness in comprehending the biological and pharmacological effects of menthol. TRP channels have been demonstrated to mediate the cooling actions of menthol. There has been new evidence demonstrating that menthol can significantly influence the functional characteristics of a number of different kinds of ligand and voltage-gated ion channels, indicating that at least some of the biological and pharmacological effects of menthol can be mediated by alterations in cellular excitability. In this article, we examine the results of earlier studies on the actions of menthol with voltage and ligand-gated ion channels.